Placental Macrophages Following Maternal SARS-CoV-2 Infection in Relation to Placental Pathology - Sharps, Megan C.; Garrod, Ainslie; Aneni, Emmanuel; Jones, Carolyn J. P.; Batra, Gauri; Heazell, Alexander E. P. (Frontiers in Virology, 2022)
In December 2019, a novel coronavirus, SARS-CoV-2, was identified. Whilst pregnant women appear to be at risk of severe infection, preterm birth and stillbirth, it is unclear whether placental dysfunction is a consistent feature of maternal SARS-CoV-2 infection during pregnancy. We aim to describe the immune response in placentas of women who had COVID-19 infection during pregnancy and investigate whether there are any associated morphological changes. The placentas of women testing positive for COVID-19 during their pregnancy were compared to contemporaneous controls who were not known to have had COVID-19 during pregnancy. Samples of each placenta were sent for histopathological analysis or underwent immunohistochemical staining for CD163, CD20, CD3, CD31 and SARS-CoV-2 spike protein. A subset of samples were sent for transmission electron microscopy. There was a significant increase in the number of CD163+ macrophages in the Post COVID group (p=0.0020). There was no difference in the percentage of CD3+, CD20+ cells, but there was an increase in placental vascularity in the Post COVID group compared to controls (p=0.026). There were no structural differences observed between the samples sent for EM analysis. However, one of the placentas from the Post COVID group was seen to have several large sub-apical vacuoles in the syncytiotrophoblast. We did not observe any virions within the vacuoles and SARS-CoV-2 spike protein staining was negative for the sample. Histopathological investigations indicated that there was no specific placental pathology caused by maternal COVID-19 infection in this cohort of samples. This study did not confirm previous studies which describe a possible increase in cases of both maternal and fetal vascular malperfusion, and placentitis in women who had COVID-19, which were seen in association with adverse pregnancy outcomes. It remains unclear whether observed abnormalities are caused by maternal infection, or whether maternal infection exacerbates existing placental pathology; understanding why some placentas generate these abnormalities is a key goal.